The Right to be Forgotten: Regulation of Personal Data Deletion in Indonesia - Ni Kadek Dhea Ardi Prabasari; Kadek Januarsa Adi Sudharma; Michael Angelo (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
The purpose of this paper is to analyze the regulation of personal data deletion in Indonesia as a form of protection for the right to be forgotten, and subsequently, the process of personal data deletion that exists in Indonesia. This paper discusses in detail the right to be forgotten. The research method used in this paper is normative legal research. It employs a conceptual approach and a legislative approach. The exploration of legal materials is conducted through document studies. The analysis in this paper is qualitative. The results of this research explain that the concept of the